Analyzing Small and Medium-Sized towns in the light of their constraints and opportunities - the case of Nevers (Burgundy - France) - Françoise Navarre; Aurelien Delpirou (European Regional Science Association (ERSA), 2014)
While small and medium-sized towns are profoundly rooted in the national territorial narrative (Delpirou, 2013), their role and position in France are not clearly identified, either in terms of territorial planning policy or in the field of academic research. And yet these "intermediate" spaces (Larmagnac, George-Marcepoil, Aubert, 2012) or spaces of "intermediation" (De Roo, 2005) have specific characteristics that set them apart from the territories that polarize the current prevailing rhetoric, which tends to be focused on either the future of metropolitan spaces or the fate of rural areas. This relative absence of small and medium-sized towns in action and analysis frameworks is in part linked to the difficulty these communities have in establishing a role for themselves. As things stand, the territorial development policies that are implemented in these towns often seek inspiration from those of metropolitan areas: they feature objectives such as establishing a presence in major trade flows and on the globalization stage. And yet these towns are places that are dependent on the historic relationships established with their rural hinterlands, particularly in terms of the range of services they provide, and at the same time embedded in polycentric networks that link them to both small towns and regional centres (with which they enjoy close links) alike. Divided as they are between these diverse, even opposing, dynamics, and between objectives that favour economic efficiency on the one hand and social or territorial equity on the other, small and medium-sized towns struggle to formulate coherent strategies. How can the various imperatives at play be reconciled? This question is all the more pressing in view of the recent economic ups and downs, which have revealed the vulnerabilities of intermediate spaces (Davezies, 2012). The weaknesses of the production sector and more or less latent political and social tensions have come to the fore with vigour, forcing small and medium-sized towns to profoundly redefine their role within economic systems, together with their local policies and development strategies. Against this backdrop, we propose to analyse the ways in which the different tensions evoked manifest themselves in a specific context, namely that of the built-up area of Nevers (60,000 inhabitants) in the west of Burgundy. Following two years of field studies, we have been able to identify the unique and emblematic characteristics of this urban area. Our paper will aim to explain the contradictory forces and the constraints that hinder the formalization and implementation of a territorial development strategy. It will shed light on the obstacles that prevent the urban area from asserting its centrality of the urban area and maintaining its role as the driving force of local dynamics. In parallel, we shall underline the singular opportunities and assets that Nevers offers, and which are likely to encourage the emergence of its own specific mode of development and governance.
Keywords: 330